2005
DOI: 10.1002/ana.20530
|View full text |Cite
|
Sign up to set email alerts
|

Selective vulnerability of preterm white matter to oxidative damage defined by F2‐isoprostanes

Abstract: Periventricular white matter injury (PWMI) is the leading cause of cerebral palsy and chronic neurological disability in survivors of prematurity. Despite the large number of affected children, the pathogenetic mechanisms related to PWMI remain controversial. Through studies of 33 human autopsy brains, we determined that early PWMI was related to oxidative damage that particularly targeted the oligodendrocyte lineage, whereas other neuronal and glial cell types were markedly more resistant. F(2)-isoprostanes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
215
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 225 publications
(236 citation statements)
references
References 63 publications
18
215
1
1
Order By: Relevance
“…Early cells of the human oligodendroglial lineage are a primary target of injury in PWMI (Back et al, 2005;Haynes et al, 2003). Major features of the early degeneration of these cells have been replicated in perinatal rodent models of acute hypoxiaischemia (Back et al, 2002a;Follett et al, 2000;Lin Ness et al, 2004;Ness and Wood, 2002).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Early cells of the human oligodendroglial lineage are a primary target of injury in PWMI (Back et al, 2005;Haynes et al, 2003). Major features of the early degeneration of these cells have been replicated in perinatal rodent models of acute hypoxiaischemia (Back et al, 2002a;Follett et al, 2000;Lin Ness et al, 2004;Ness and Wood, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…These cells suffer rapid necrotic death when exposed to ischemic conditions in cell culture (Fern and Moller, 2000), and in isolated optic nerve , and are selectively lost after ischemia in vivo (Back et al, 2002a;Follett et al, 2000;Lin et al, 2004;Liu et al, 2002); (Ness et al, 2001). The sensitivity of late precursor cells (pre-oligodendrocytes) and immature oligodendrocytes to ischemic injury is associated with a limited capacity to resist oxidative stress (Back et al, 1998(Back et al, , 2005Baud et al, 2004a;Bernardo et al, 2003;Haynes et al, 2003), and with the expression of Ca 2 + -permeable non-N-methyl-D-aspartate (NMDA)-type glutamate receptors on the somata (Fern and Moller, 2000;Follett et al, 2000;Wilke et al, 2004). Recent findings have revealed that the processes of immature oligodendrocytes also express NMDAtype glutamate receptors that mediate early disintegration of these structures under ischemic conditions (Káradó ttir et al, 2005;Salter and Fern, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…15 Indeed, we have shown that IPCs in the oligodendroglial lineage are especially vulnerable to hypoxic/ischemic injury of newborns. 16 A similar situation may exist for IPCs in the neuronal lineage that reside within specialized brain regions, known as neurogenic niches, that include the subgranular zone (SGZ) and the subventricular zone. [17][18][19] Expression of transcription factors is now being used to identify the different proliferating cell populations in adult mouse SGZ neurogenesis; indeed the sequential expression of these transcription factors precisely recapitulates that observed in embryonic neocortical neurogenesis.…”
Section: Lipopolysaccharide (Lps)-induced Innate Immune Activation Lementioning
confidence: 93%
“…The timing of appearance of late oligodendrocyte progenitors (preOLs) coincides with the high-risk period for PWMI . Early PWMI lesions display significant lipid peroxidation injury that results in pronounced degeneration of human preOLs (Haynes et al, 2003;Back et al, 2005).…”
Section: Introductionmentioning
confidence: 99%